A sensitive liquid chromatography–tandem mass spectrometry method for quantitative bioanalysis of fingolimod in human blood: Application to pharmacokinetic study. (15th April 2020) - Gopinath, R.; Narenderan, S. T.; Kumar, M.; Babu, B.
Abstract: A simple and sensitive liquid chromatography–tandem mass spectrometry (LC–MS/MS) method has been developed and validated for the determination of fingolimod in human blood. The analyte and internal standard fingolimod‐d4 were extracted from 300 μl of human blood using protein precipitation coupled with solid‐phase extraction method. The chromatographic separation was achieved with a Kinetex biphenyl column (100 × 4.6 mm, 2.6 μm) under isocratic conditions at the flow rate of 0.8 ml/min and column temperature was maintained at 45°C. The detection of analyte and internal standard was carried out by tandem mass spectrometry, operated in positive ion and multiple reaction monitoring acquisition mode. The method was fully validated for its selectivity, precision, accuracy, linearity, stability, detection and quantification limit. The extraction recovery of fingolimod in human blood ranged from 98.39 to 99.54%. The developed method was linear over the concentration range of 5–2500 pg/ml with a detection limit of 1 pg/ml. The developed method was validated and successfully applied for pharmacokinetic study after oral administration of fingolimod capsules.